How Computers Hurt Modern Language - Abduolimova, Maftunakhon; Munisa, Abdullayeva (Journal of Innovation in Education and Social Research, 2024)
Computers have undoubtedly had a significant impact on modern language, both positive and negative. While they have certainly improved communication and accessibility, they have also presented challenges that can be detrimental to language development.